2016
DOI: 10.1093/neuonc/now164
|View full text |Cite
|
Sign up to set email alerts
|

A novel 3D human glioblastoma cell culture system for modeling drug and radiation responses

Abstract: Background.Glioblastoma (GBM) is the most common primary brain tumor, with dismal prognosis. The failure of drug–radiation combinations with promising preclinical data to translate into effective clinical treatments may relate to the use of simplified 2-dimensional in vitro GBM cultures.Methods.We developed a customized 3D GBM culture system based on a polystyrene scaffold (Alvetex) that recapitulates key histological features of GBM and compared it with conventional 2D cultures with respect to their response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
111
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(128 citation statements)
references
References 38 publications
17
111
0
Order By: Relevance
“…Such co‐option mechanisms, widely documented in clinical specimens, have been shown to compromise the efficacy of treatments that either target angiogenesis or promote vascular normalization or integrity in both primary and metastatic tumors. Consistent with the clinical context, G7 tumor cells have been shown to express VEGF both in vivo and in vitro; hence, angiopoiesis is expected close to the tumor core. Here, investigating at earlier stages of tumor development allowed minimizing the effects related to tumor angiogenesis or necrosis.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Such co‐option mechanisms, widely documented in clinical specimens, have been shown to compromise the efficacy of treatments that either target angiogenesis or promote vascular normalization or integrity in both primary and metastatic tumors. Consistent with the clinical context, G7 tumor cells have been shown to express VEGF both in vivo and in vitro; hence, angiopoiesis is expected close to the tumor core. Here, investigating at earlier stages of tumor development allowed minimizing the effects related to tumor angiogenesis or necrosis.…”
Section: Discussionsupporting
confidence: 57%
“…The animals were intracranially injected with G7 cells (10 5 cells per mouse) into the subventricular zone using stereotactic equipment. 20 Study outcomes are reported following the ARRIVE guidelines. 21 Ten animals were scanned 9 and 12 weeks after GBM cell injection.…”
Section: Tumor Model and Experimental Designmentioning
confidence: 99%
“…Gomez-Roman et al, 2017 tested temozolomide, bevacizumab and erlotinib on 2D and 3D Glioblastoma cultures. They proved that these three drugs affect 2D and 3D cultures and 3D model responses were similar to clinical trials 84 . In a recent study by Ribas et al, 2016, the authors created a vascular microenvironment of the heart for drug development 85 .…”
Section: D Cell Culture Modelssupporting
confidence: 53%
“…However, this study underlines the need for better predictive in vitro models. Multiple studies suggest that drug responses of 2D cell cultures poorly predict the outcome of clinical studies (Aljitawi et al, 2014;Bhadriraju & Chen, 2002;Edmondson, Broglie, Adcock, & Yang, 2014;Gomez-Roman et al, 2017;Guengerich, 2007;Hingorani et al, 2009;Ramaiahgari et al, 2014;Ravi, Paramesh, Kaviya, Anuradha, & Solomon, 2015;Weaver et al, 1997).…”
Section: Introductionmentioning
confidence: 99%